Endoplasmic reticulum stress and apoptosis - Faitova, Jitka; Krekac, Daniel; Hrstka, Roman; Vojtesek, Borivoj (Cellular & molecular biology letters, 2006)
Cell death is an essential event in normal life and development, as well as in the pathophysiological processes that lead to disease. It has become clear that each of the main cellular organelles can participate in cell death signalling pathways, and recent advances have highlighted the importance of the endoplasmic reticulum (ER) in cell death processes. In cells, the ER functions as the organelle where proteins mature, and as such, is very responsive to extracellular-intracellular changes of environment. This short overview focuses on the known pathways of programmed cell death triggering from or involving the ER.
Keywords: Animals; lidé; Apoptosis; Protein Folding; oxidační stres; sbalování proteinů; signální transdukce; endoplazmatické retikulum; Oxidative Stress; Signal Transduction; Humans; apoptóza; zvířata; Endoplasmic Reticulum